Layers of Connection: info and ideas graphic ... - Williams, Cassie; Blom, Simone M; Crinall, Sarah Maree (Southern Cross University, 2025)
The Layers of Connection info and ideas graphic was created as a teaching and learning resource to support and facilitate the inclusion of First Nations Science alongside western science in a first-year undergraduate science education unit in the Faculty of Education at Southern Cross University. This resource is based on the findings of a critical literature review and funded by the Faculty of Education Teaching and Learning Grants Program. ...